Branding Corporate Social Responsibility: A Case Study on Public-Listed Telecommunication Companies in Malaysia - Ahmad, Jamilah (Registrar of Newspapers for India (RNI), 2019)
Corporate social responsibility (CSR) is a pillar for any organization to portray the positive reputation of the organization to the public. The image and commitment of CSR initiatives reflect the corporate brand of the organization. This study aims to have a better understanding of brand and CSR from the role of public relations practitioner involving two telecommunication companies namely Maxis Berhad and Axiata group which are public-listed companies in Malaysia. A qualitative indepth interview was carried out with both public relations senior practitioners. Findings indicated that public relations practitioners from both telecommunication companies have a common understanding of branding CSR within the respective company. Despite, the differences in the basis of branding CSR, it is also found that CSR plays an important role to strengthen the corporate brand.